Conceptualisation Of Corporate Waqf - Abdullaah Jalil; Asharaf Mohd Ramli (Universiti Sains Islam Malaysia, 2024)
Corporate waqf is usually considered as the component of cash waqf. However, Hajar et al (2011) suggested that corporate waqf should be established as an independent wadf concept. Thus, based on the suggestionm, this paper aims to reconceptualize corporate as an independent waqf concept. This paper is a theoretical study based on previous studies and researches on corporate waqf. The paper discussess corporate waqf from three different aspects; definition of corporate as independent waqf concept, models, and Shariah considerations. The study will establish corporate waqf as an independent category of waqf due to its salient characteristics and extend the understanding and concept of the corporate waqf. The novelty of this study lies on its attempt in defining the corporate waqf independently. This study also discuss the three models of the corporate waqf and deliberate on the main Shariah considerations related to the corporate waqf practice.